(untitled) (World Science, 2024)
Over the years, the regulatory framework related to the construction industry in Bulgaria has undergone a number of changes and gradually creates legal prerequisites for the construction of the green system in the settlements. All this, combined with the construction boom and the continuous migration of people to the big cities, leads to serious challenges that must be overcome over the years in order to be able to establish the specialty "Landscape Architecture" and justify the need for it for the quality of life in Bulgarian cities.